English Language Teachers’ Perceptions and Experiences on Formative Assessment in Nepal - Kafle, Gita; Neupane, Bharat Prasad (KMC Journal, 2025)
This study explores English language teachers’ perception of formative assessment, their execution in the classroom, and the opportunities and challenges they faced while implementing it. We employed narrative inquiry to investigate the formative assessment practices of teachers working in public schools in Kathmandu. Four teachers from two public schools were purposively selected. We interviewed them to derive in-depth information on formative assessment. Later, we analyzed the interview transcript thematically. The findings highlight significant obstacles such as teachers’ unpreparedness, infrastructure limitations, and alignment issues with curriculum guidelines. Despite these challenges, formative assessment positively impacts student learning outcomes by fostering engagement and personalized learning experiences. The study recommends targeted teacher training, resource allocation and policy alignment to optimize formative assessment practices in the public schools in Nepal.